Pristionchus Scratchpads—an online platform for taxonomy, systematics and phylogeny - Herrmann, Matthias; Neuner, Jonas; Voetsch, Martin; Wörner, Johannes; Kanzaki, Natsumi; Sommer, Ralf J. (Zootaxa, 2015)
The availability of molecular tools has transformed animal taxonomy and systematics in the last two decades. In particular, small animals that have few morphological diagnostic attributes can be identified and diagnosed accurately by adding molecular markers to those already used. In nematodes, molecular sequence information relevant for taxonomy and systematics is currently transforming the resolution of phylogenetic studies. The extensive use of molecular tools is associated with a large increase in the number of publications. This increase can make problematic accessing current knowledge comprehensively. Similarly, old publications in very specialized journals are often hard to access as well. To overcome some of these issues for the nematode genus Pristionchus, we introduce Pristionchus Scratchpads as an online platform for taxonomy, systematics and phylogeny. As an online database, Pristionchus Scratchpads is community driven, searchable, comprehensive and dynamic. Given the substantial effort in using Pristionchus pacificus and other Pristionchus species as model systems in evolutionary biology, Pristionchus Scratchpads is intended to facilitate the development of new online tools in nematode taxonomy and systematics.